Area-Based Development, Local Institutions and Climate Adaptation : Comparative Analysis from West Africa and Latin America - Agrawal, Arun; Mearns, Robin; Perrin, Nicolas; Kononen, Minna (World Bank, Washington, DC, 2017)
This report on adaptation to climate variability and change draws together the conclusions of a series of comparative case studies undertaken for the Area-Based Development and Climate Change (ABDCC) project of the Social Development Department of the World Bank. The report contributes to a better understanding of pro-poor adaptation by addressing the growing need for systematic analyses of existing rural adaptation strategies in the face of climate variability. The study shows: 1) how different types of climate phenomena affect households that are already vulnerable owing to their political-economic and social circumstances, 2) the ways in which households cope with and adapt to climate hazards, and 3) the role of rural organizations and institutions in helping vulnerable households cope with climate impacts and other sources of vulnerability more effectively. The study also complements other macro-level analyses in which the focus is primarily on government policies in the context of adaptation. The ABDCC study relied on four strategies for its implementation, data collection, and capacity building efforts: 1) review of secondary information and the selection of study sites; 2) data collection through household, focus group, and expert interviews; 3) data analysis and identification of feasible policy options; and 4) capacity building and dissemination of results. The study generated data both from secondary sources as well as primary research. The data was used to prepare country reports and policy notes but has also been analyzed using basic statistical methods to understand the relationship between institutions, adaptation strategies, and social groups within communities and territories.